Resources for Families during COVID-19: A Content Analysis of Information Provided on School District Web Sites. Issue 4 (21st April 2021) - Iachini, Aidyn L; Childs, Tasha M
Abstract: The novel coronavirus (COVID-19) pandemic has disrupted the educational system not only in regard to teaching and learning, but also in relation to the other services and supports (mental health services, meal and nutrition programs, and so on) provided to students and families. School district Web sites are critical access points for families during this crisis to learn information about key resources being provided during school closure. This study used content analysis to examine whether school district Web sites in one southeastern state provided information about COVID-19 and 11 other resources. Findings indicate that about half of the Web sites provided both COVID-19 information and additional resources. Few districts provided information on resources for students with disabilities, a subgroup of students at heightened vulnerability during this time of virtual learning. Approximately a third of school district Web sites provided no information on COVID-19 or any of the other resources. The article concludes with a discussion of the implications for school social workers related to crisis response and leadership around contributing to efforts that aim to address educational disparities and inequities and maximize student success during this time of crisis.